Algorithmic Maps and the Political Geography of Early-modern Japan - Mark Ravina (Journal of Cultural Analytics)
Many of our conventional mapping practices are ill-suited to the complexities and nuances of pre-modern politics, especially in the non-Western world. Choropleth maps suggest that political borders are clear and uniform, but early modern politics was characterized by ill-defined and overlapping political spheres. This study uses interactive maps to explore the case of composite state borders in early modern Japan. Using points, rather than polygons, to represent villages, we reproduce how Tokugawa-era officials understood political space primarily as population nodes, not as clearly defined polygons. In lieu of conventional borders, we calculate Voronoi polygons to show where political authority was spatially fragmented. Using logit analysis we show that increased spatial contiguity allowed lords (daimyo) to establish monopolies and tax their holdings more intensively. Other factors, such as the lord’s rank, figure prominently in the historiography, but can not be substantiated in our analysis.